RASIO TEPUNG TERIGU DAN TEPUNG KACANG TUNGGAK (Vigna unguiculata) DALAM PEMBUATAN CRACKERS - Kandhi Darmatika; Akhyar Ali; Usman Pato (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Cowpea crackers are one type of biscuit made from a mixture of cowpea flour dough and wheat flour through a fermentation process. This study aimed to obtain the best ratio of cowpea flour additon to the qualityof crackers in accordance with SNI 01-2973-1992. The research method used a CompletelyRandomized Design (CRD) experiment consisting of 5 treatments and3 repetitions. The treatments of cowpea additon consisted of TKT0 (ratio of 100% wheat flour and cowpea flour 0%), TKT1(ratio of 90% wheat flour and cowpea flour 10%), TKT2 (ratio of 80% wheat flour and cowpea flour 20%), TKT3(ratio of 70% wheat flour and cowpea flour 30%) and TKT4(ratio of 60% wheat flour and cowpea flour 40%) of 100 g of material weight. The data were analyzed statistically by ANOVA, and then continued by Duncan's New Multiple Range Test (DNMRT) at 5% level. The results showed that ratio of wheat flour and cowpea flour significantly affected moisture, ash and protein contents, as well as colour, aroma, taste, texture and overall acceptance. The best treatment was TKT4(ratio of 60% wheat flour and cowpea flour 40%). The product had moisture content5.32%, ash of 1.76%, protein 9.26%, color 4.17 (brown), 3.87 (aroma of cowpea), taste 3.93 (taste Cowpea), texture 3.57 (crunchy) and overall rating with a score of 3.75 (like). Keywords: Wheat Flour, cowpea flour, crackers, ratio.